Validation of the Neutron Monitor Yield Function Using Data From AMS‐02 Experiment, 2011–2017. Issue 4 (2nd April 2019) - Koldobskiy, Sergey A.; Bindi, Veronica; Corti, Claudio; Kovaltsov, Gennady A.; Usoskin, Ilya G.
Abstract: The newly published spectra of protons and helium over time directly measured in space by the Alpha Magnetic Spectrometer (AMS‐02) experiment for the period 2011–2017 provide a unique opportunity to calibrate ground‐based neutron monitors (NMs). Here, calibration of several stable sea level NMs (Inuvik, Apatity, Oulu, Newark, Moscow, Hermanus, and Athens) was performed using these spectra. Four modern NM yield functions were verified: Mi13 (Mishev et al., 2013, https://doi.org/10.1002/jgra.50325 ), Ma16 (Mangeard et al., 2016, https://doi.org/10.1002/2016JA023515 ), CM12 (Caballero‐Lopez & Moraal, 2012, https://doi.org/10.1029/2012JA017794 ), and CD00 (Clem & Dorman, 2000, https://doi.org/10.1023/A:1026508915269 ), on the basis of the cosmic ray spectra measured by AMS‐02. The Mi13 yield function was found to realistically represent the NM response to galactic cosmic rays. CM12 yield function leads to a small skew in the solar cycle dependence of the scaling factor. In contrast, Ma16 and CD00 yield functions tend to overestimate the NM sensitivity to low‐rigidity (<10 GV) cosmic rays. This effect may be important for an analysis of ground level enhancements, leading to a potential underestimate of fluxes of solar energetic particles as based on NM data. The Mi13 yield function is recommended for quantitative analyses of NM data, especially for ground level enhancements. The validity of the force field approximation was studied, and it was found that it fits well the directly measured proton spectra, within a few percent for periods of low to moderate activity and up to ≈10% for active periods. The results of this work strengthen and validate the method of the cosmic ray variability analysis based on the NM data and yield function formalism and improve its accuracy. Key Points: Direct validation of the NM yield function is performed using the proton and helium spectra measured by AMS‐02 for the period of 2011‐2017 The NM yield function by Mishev et al. (2013) is fully validated, while others need revisions The use of the force field approximation to fit the measured proton spectra is validated within +/‐10%